Computer Networking in Academic Libraries in Malaysia - Chee Hong, Lim (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 4 No 1 (2536): Academic Services Journal)
Computer Networking in Academic Libraries in Malaysia